"Creatio ex nihilo" a samoistność świata - Piwowarczyk, Marek (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2009)
In this article I try to answer the question whether the thesis that some being can create autonomous objects out of nothing is compatible with Roman Ingarden's ontology. In the first part of the paper I analyse Ingardenian concepts of moments of being and modes of being. Special attention is put on the existential autonomy. The second part is devoted to ontological relation of creation. It turns out that basic theses of Ingarden's ontology exclude possibility of "creatio ex nihilo" of autonomous objects.